The Sioux - Osinski, Alice (Chicago : Childrens Press, 1984)
A brief history of the Sioux, or Dakota, Indians of the Great Plains describing their tribal organization, customs, religion, and their encounter with the white settlers.
Includes index.
Keywords: Dakota Indians -- Juvenile literature; Indians of North America